Self-reported healthy dietary behavior relates to parental attitudes on child feeding, health and diet quality. - Mäkelä, Irene (My University, 2021)
Parents influence their children´s diet greatly as seen in earlier research. In addition, it is known that both diet and obesity in childhood tend to persist and therefore affect to the risk of several chronic lifestyle related diseases in years to come. The aim of this study is to examine the parental attitudes on child feeding and it´s health dependency and the differences between parents, who self-perceived to follow a healthy diet to those who do not. Also, differences in child’s diet quality and prevalence of obesity were compared between the groups. The significance is to learn more about these factors so that the information would be benefited on child health clinics nationwide. Altogether, 738 parents with their 2- to 6-year-old child were included to the study. Children´s diet quality was assessed by a validated index (Children’s Index of Diet Quality, CIDQ). Information was collected in the children´s regular visits in child health clinics by a semi-structured questionnaire, which included the sources of information influencing feeding, the diverse factor´s that parents consider whilst feeding their child, the parental attitudes on child feeding and health in addition to the parental background factors. Nurses in the child health clinics measured and reported the heights and weights of the children. The parents were divided into two groups; health-conscious (HC) (n = 396) and non-health-conscious (non-HC) parents (n = 342) based on their self-perceived report to follow a healthy diet and the differences between parents were statistically analyzed. Study demonstrated that HC-parents were more aware of the long-time health effect of the childhood diet. Further, they considered the health and nutrition factors more often in the feeding situation, and their children’s diet quality was also better than the non-HC-parents´ children’s diet. The HC-parents´ children were more often underweight or normal weight, as compared to the non-HC-parents´ children, who were more commonly overweight or obese. This study supports earlier observations about the importance of parents´ attitudes and feeding habits regarding their child´s diet and it´s health dependency, as for we suggest them to affect to the children´s diet. The concept of programming later health by childhood nutrition was seen rather important in both groups, but more wide knowledge would be preferable. These results underline the importance of conversation between the health care professionals and parents about their food related attitudes. In addition, the encouragement of parents to pay attention to their own diet (concept of positive parental role modelling) would be beneficial for responding the urgent need of improvement of childhood diet quality.
Keywords: Preschool child, parental attitude, health, diet.